(untitled) (Global Journal of Medical Research, 2015)
Objectives: The aim of this study was to reveal the mode of presentation of coronary artery disease(CAD) and the outcome of coronary artery bypass graft surgery(CABG) Methods: This was a retro - prospective study conducted in El shaab and Ahmed Gasim Hospitals from 201 2 to 2015. Fifty nine patients were included in the study of whom 49(83.1%) were males and 10(16.9%) were females. The study variables included; patients demographics, etiological risk factors, form of presentation, blood and imaging investigations, indica tions for coronary artery bypass graft (CABG) surgery, modalities of CABG surgery, prognostic risk factors and outcome of CABG.